Profit from the positive proven leadership strategies to boost productivity and transform your business - Margaret Greenberg and Senia Maymin (New York Mcgraw-Hill, 2013)
You've streamlined processes. You've restructured. You?ve sought customer and employee feedback. You've tried everything. Now, try something that works. Profit from the Positive is a practical, groundbreaking guide for business leaders, managers, executive coaches, and human resource professionals. Whether you lead three employees or 3,000, this book shows you how to increase productivity, collaboration, and profitability using the simple yet powerful tools from the new field of Positive Psychology.
Includes bibliographical references (pages 197-211) and index.
Keywords: Leadership